Empowering women through home culinary business at baking lovers community (BLC) Samarinda - Norvadewi Norvadewi; Akhmad Nur Zaroni (Faculty of Economics and Business Mulawarman University, 2022)
Today women's empowerment is seen as an essential component in development and poverty reduction. Women's empowerment makes women independent and confident. They will have the ability to turn their choices into desirable actions, which will lead to the emergence of economic, political, social, and psychological empowerment. One way of empowering women is through community or group (self-help groups). Women's empowerment through this community is in Baking Lovers Community (BLC) Samarinda, a community of women who have similar hobbies that are culinary fields with home businesses that they run. This research is descriptive qualitative research. The study was conducted on the home- based culinary business community incorporated at Baking Lovers Community of Samarinda City. This research aims to find out the economic empowerment program in the BLC community, how the impact of empowerment on the development of culinary businesses in the city of Samarinda, and what obstacles they face in the empowerment of women in the community. Data collection techniques are conducted with Focus Group Discussion (FGD), interviews with BLC administrators and members, and documentation. Validity data using triangulation. As for data analysis using the Miles and Huberman models, data reduction, data presentation, and conclusion withdrawal. The economic empowerment program in BLC's is of various training to improve members' culinary skills, such as training together with baking cakes, bringing in chefs, photography training to support product promotion, product promotion on Social Media Fb and Instagram, sharing culinary recipes, social activities and charity bazaars, facilitating members to take care of business licenses and halal certification of products. The business potential developed is making the various artificial types of cakes and food, both modern and traditional, for multiple events, catering, and buffets. The empowerment programs of BLC are to be as a source of income, hobby development, knowledge sharing, business continuity, product innovation, packaging and brand innovation, and digital marketing development. Thus, this empowers them as subjects/actors actively involved in the story, empowered to manage businesses independently, and organizations that accommodate them play a role in charge. The obstacles faced are the uneven ability of human resources, capital to develop companies, business licensing, and halal certification.